2022
DOI: 10.1007/s13132-021-00856-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Employability of Business Graduates: Evidence from Woldia University

Abstract: The main purpose of the study is to explore the employability of business graduates through the mediating effect of level of competency with reference to Woldia University business graduates. In this study, a cross-section research design was applied and a quantitative research approach was followed. The data was collected by using questionnaires from the sample of 223 business graduates. The respondents were selected by using the systematic random sampling technique. The collected data were analyzed through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The study further suggested that to enhance graduates' skills, higher education institutions (HEIs) and employers must collaborate so that graduates can better adapt to the changing nature of the labour market and increase their employability. The present study's findings were also supported by recent studies (Kassa, 2022;Hossain et al, 2020;Mainga et al, 2021), who posited that employability skills are crucial in a changing labour market. Further, graduates in the study viewed that business schools have a significant role in fostering the students' employability skills.…”
Section: Perception Of Graduates Toward Role Of Business Schools In E...supporting
confidence: 89%
See 1 more Smart Citation
“…The study further suggested that to enhance graduates' skills, higher education institutions (HEIs) and employers must collaborate so that graduates can better adapt to the changing nature of the labour market and increase their employability. The present study's findings were also supported by recent studies (Kassa, 2022;Hossain et al, 2020;Mainga et al, 2021), who posited that employability skills are crucial in a changing labour market. Further, graduates in the study viewed that business schools have a significant role in fostering the students' employability skills.…”
Section: Perception Of Graduates Toward Role Of Business Schools In E...supporting
confidence: 89%
“…A considerable number of studies on graduate employability have been conducted recently. For instance, Kassa (2022) investigated the level of competency among Woldia University business graduates as a moderating factor in the graduates' employability. A cross-sectional study design and quantitative methods were used for this investigation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As proved by Hong et al (2023), this finding showed that self-efficacy acts as the utmost significant predictor towards students' satisfaction with the major, followed by perceived curriculum and campus support. Supported by Kassa (2022), self-efficacy has statistically significant positive effect on the employability of business graduates because it had a positive statistically significant effect on the employability of graduates. Additionally, group assessments have been counted into the curriculum for decades, responding to employers' demands of developing employability skills in project management university graduates (Tumpa et al, 2023).…”
Section: Challenges Faced By Graduates Entering Job Marketmentioning
confidence: 94%
“…In Sub-Saharan countries, the rate of graduate employability is rapidly declining in spite of the skills and competencies of graduates [1]. Twinoburyo et al [2] have shown that Sub-Saharan countries have the highest unemployment rate in the world with an average of 7%, and the majority of those who are employed in such countries have substandard jobs.…”
Section: Introductionmentioning
confidence: 99%